Reconstructing the Concept of Copyright as Al-Ḥuqūq Al-Māliyah in Islamic Law - Tarmidzi, Tarmidzi; Inayati, Anindya Aryu; Asro, Muhmmad; Jumailah, Jumailah (Institut Agama Islam Negeri Ponorogo, 2025)
Copyright, as part of intellectual property rights, has become a growing issue in Islamic law, especially regarding its ownership classification. While positive law recognizes copyright as an economic right that can be transferred and inherited, Islamic law presents differing views on whether it falls under huquq al-adabiyah (moral rights) or huquq al-mãliyah (economic rights with material value). This debate arises from the traditional Islamic view of ownership, which emphasizes tangible assets. With the rise of creative industries and technological advancements, there is an urgent need to reconstruct copyright as huquq al-mãliyah to ensure proper legal protection. Within the framework of maqasid al-shariah, acknowledging copyright as an economic right aims to safeguard individual ownership, prevent exploitation, and promote innovation. This study employs a qualitative method with a normative juridical approach, examining classical and contemporary fiqh literature alongside copyright regulations in Muslim-majority countries. The analysis applies inductive-deductive and comparative techniques between Islamic and positive law. Findings show that copyright meets the criteria of huquq al-mãliyah due to its economic value, transferability, and inheritability. Islamic legal sources—including the Qur’an, Hadith, and scholarly interpretations—support its recognition. This reconstruction offers significant implications for strengthening copyright protection within Islamic legal frameworks and developing shariah-compliant regulations suited to modern economic contexts.